"Statisticians are particularly attuned to the beauty of uncertainty". Issue 4 (27th July 2022) - Britten, Anna
Abstract : Data visualisation fans will need no introduction to David McCandless, data journalist and author of the bestselling books Information is Beautiful and Knowledge is Beautiful as well as, most recently, Beautiful News . He is also one of the media's most called‐upon advocates for statistics as art, and tells Anna Britten about his process, data viz heroes and why communication is all about context Abstract : Data visualisation fans will need no introduction to David McCandless, data journalist and author of the bestselling books Information is Beautiful and Knowledge is Beautiful as well as, most recently, Beautiful News. He is also one of the media's most called‐upon advocates for statistics as art, and tells Anna Britten about his process, data viz heroes and why communication is all about context